The SAGE handbook of governance - Bevir, Mark. (Los Angeles, California SAGE, 2011)
While the verb 'to govern' and the noun 'government' are well established terms, 'governance' is relatively new to social science vocabulary. This book is a welcomed contribution to a clearer understanding of this emerging concept.
Keywords: Policy sciences; Public administration -- Philosophy